Refusal of Itsbat Nikah Pleading Due to an Invalid Guardian According to Islamic Law (Determination Number 49/Pdt.P/2021/PA.Mkm) - Maharani, Aisyah; Ani Yumarni; Yoelianto (Fakultas Hukum Universitas Djuanda, 2025)
This is written in Article 14 of the Compilation of Islamic Law that a legitimate guardian must meet certain requirements, such as a lineage guardian or a judge guardian who has the position and right to marry the prospective bride. In carrying out a marriage, marriage registration is very important to be carried out in the presence of and directly supervised by the Marriage Registrar so that a marriage certificate or book can be issued. Marriages that are carried out outside the supervision of the Marriage Registrar do not have legal force and are not recorded or are commonly called clandestine marriages. If a husband and wife who are married clandestinely want to get a marriage book, they must request a marriage ratification application to the Religious Court or commonly called Itsbat Nikah. In the Application for Determination Number 49/Pdt.P/2021/PA.Mkm. the author examines the Rejection of the Application for Itsbat Nikah due to an Invalid Guardian. In this study, the author uses the normative legal research method. The results of this study reveal that the rejection of the application for itsbat nikah by the Judge was because the marriage guardian in the applicants' marriage was the applicant's neighbor and was not a person who was legally entitled to marry, namely the lineage guardian or the judge's guardian. The legal consequence of the rejection is that the applicants' marriage becomes invalid and is automatically canceled in the context of Islamic marriage law. This is because the applicants ignored the provisions of the pillars and valid requirements of marriage, especially regarding the marriage guardian.